PF.21 Brain Abnormalities and Neurodevelopmental Delay in Congenital Heart Disease: Systematic Review and Meta-Analysis. (26th April 2013) - Khalil, A; Suff, N; Grande, A; Carvalho, J; Cooper, D; Thilaganathan, B
Abstract : Objectives: Studies have demonstrated an association between congenital heart disease (CHD) and neurodevelopmental delay, partly attributed to the risk of brain injury during cardiac surgery. However, neuroimaging studies have demonstrated a high incidence of preoperative brain abnormalities. The aim of this study was to perform a systematic review in order to quantify the non-surgical risk of brain abnormalities and neurodevelopmental delay in fetuses/newborns with CHD. Methods: MEDLINE, EMBASE and The Cochrane Library, without language restrictions were searched electronically, utilising combinations of the terms congenital heart, cardiac, neurologic, neurodevelopment, MRI, ultrasound, neuroimaging, autopsy, preoperative and outcome. Reference lists of relevant articles and reviews were hand searched for additional reports. Cohort and case-control studies were included. Case reports and editorials were excluded. Between-study heterogeneity was assessed using the I2 statistic. Results: The search yielded 9, 129 citations. Full manuscripts were retrieved for 119, and 30 were included in the review and meta-analysis. 21 studies (n = 953) have reported brain abnormalities in fetuses, newborn or infants with CHD, either preoperatively or in those who did not undergo congenital cardiac surgery. The remaining 9 studies (n = 512) have reported preoperative data on neurodevelopmental assessment in newborn or infants with CHD. The prevalence of brain abnormalities was 36% (95% CI, 26%, 47%; I² = 90.5%) and of the neurodevelopmental delay 42% (95% CI, 34%, 51%; I² = 68.9%), though with heterogeneity between studies. Conclusions: In the absence of chromosomal or genetic abnormalities, fetuses with CHD are at increased risk of brain abnormalities and neurodevelopmental delay, which are independent of the surgical risk.